A New Antiviral Regimen Against SARS-CoV-2 Based on Nanoviricide’s Biopolymer (NV-CoV-2) - Chakraborty, Ashok; Diwan, Anil; Barton, Randall; Arora, Vinod; Thakur, Yogesh; Chiniga, Vijetha; Tatake, Jay; Pandey, Rajesh; Holkar, Preetam; Holkar, Neelam; Pond, Bethany (Frontiers in Nanotechnology, 2022)
NV-CoV-2, a nanoviricide composed of covalently attached polyethylene glycol (PEG) and alkyl pendants that are designed to bind free virion particles of most strains of coronaviruses in a broad-spectrum manner at multiple points. The multi-point binding interaction, like a nano-velcro-tape, may lead to lipid-lipid fusion of the alkyl chains in the nanoviricide micelle with the lipid envelope of the virus, thereby dismantling the virus to capsid form or further, without any involvement of the host immune system. and encapsulate the virus, disabling its ability to infect cells. This putative mechanism is orthogonal to the mechanism of action of most other anti-coronavirus agents in development. Thus, it may be possible to achieve a stronger antiviral effect by combining NV-CoV-2 therapy with other anti-coronavirus therapies like Remdesivir (RDV). Further, some ligands similar to the S-protein of SARS-CoV are designed by molecular modeling and attached to nanoviricide at the same site as where the cognate cellular receptor, ACE2, binds, therefore a competitive binding inhibition may result. Nanoviricide can encapsulate another antiviral compound, here RDV we used, and protect it from serum-mediated degradation in vivo, thereby making it available for a longer period of time to interact with RNA polymerase and inhibits.